DEVELOPMENT OF PORTER GENERIC STRATEGY MODEL FOR SMALL AND MEDIUM ENTERPRISES (SME’s) IN DEALING WITH ASEAN ECONOMICS COMMUNITY (AEC) - Julita Julita, S.E., M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
In welcoming the ASEAN Economic Community (AEC), we will enter a new phase with our neighboring partner countries, especially ASEAN members. One of the main pillars of the MEA is the free flow of goods, so that in 2015 trade in goods in the ASEAN region is done freely without any obstacles, tariff and non-tariff. The AEC applies the Common Effective Preferential Tariff (CEPT) scheme previously applied at the Asean Free Trade Area (AFTA), i.e. a gradual tariff reduction for certain types of goods conducted within the agreed timeframe. This study aims to find the problems that often hamper the development of SME's in Deli Serdang District in the competitive advantage especially in facing the AEC, for it needed a strategy in creating competitive advantage in the AEC era. Many strategies for creating competitive advantage and one of Porter's generic strategies. This strategy provides success in the company so that researchers want to adopt Porter's generic strategy for SME's especially in Deli Serdang DistrictF